Primary cutaneous nocardiosis in children. Issue 2 (19th April 2016) - Shono, Miki; Suga, Kenichi; Gonoi, Tohru; Goji, Aya; Matsuura, Sato; Inoue, Miki; Kawahito, Masami; Yoshii, Satoka; Sedo, Hiromichi; Mori, Kazuhiro
Abstract : Introduction: Reports of paediatric cases of primary cutaneous nocardiosis are rare in Japan. We report the case of a 5-year-old immunocompetent boy with primary cutaneous nocardiosis. Case presentation: One week after injuring his left knee, the boy presented with fever, pain in the left hip joint and gait disturbance. Oral administration of cephalosporin proved ineffective, and he was not able to stand due to pain in the inguinal region. On admission, swelling of the left inguinal lymph nodes and abscess with microsatellite pustules in the left knee were found. Gram-positive bacilli with branching filaments grew in the culture from the drained pustule. They were partially acid fast on Ziehl–Neelsen staining. His symptoms improved after initiating treatment with sulbactam/cefoperazon and sulfamethoxazole/trimethoprim (TMP-SMX). Nocardia brasiliensis was identified from 16S rRNA gene sequencing. TMP-SMX was administered for 5 weeks, and no relapses have occurred as of the 1-year follow-up. Conclusion: N. brasiliensis lives in soil and is the major cause of primary lymphocutaneous nocardiosis. A cutaneous abscess with surrounding microsatellite lesions and lymphadenopathy suggest the possibility of cutaneous nocardiosis. Because growth of Nocardia spp. is very slow, adequate incubation time is necessary.